ATIVIDADES PRÁTICAS INVESTIGATIVAS NO ENSINO DE BIOQUÍMICA - Milanez, Erica da Cunha Maciel (2020)
Biochemistry corresponds to a broad theme that has gained more and more space in the scientific and educational environment, however challenges exist when addressing the basic concepts of biochemistry in the classroom due to its complexity, high degree of